PEMANFAATAN ABU SERBUK GERGAJI DAN PUPUK GUANO TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN CABAI (Capsicum annum L.)DI LAHAN GAMBUT - Putra, Irwan Adi; Yetti, Husna; Ariani, Erlida (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
This study aims to look at the effect of sawdustash and guano fertilizer on the growth and production of pepper plants in peatland as well as to get appropriate dose of sawdust ash and manure guano. This research was conducted at the experimental peat garden, Faculty of Agriculture, University of Riau, RimboPanjang, Kampar. The research lasted for five months, from December 2013 until May 2014. The experiments was conducted using factorial randomized block design consisting of two factors and three repetition. The first factor is the sawdustash 10 ton / ha (4 kg/plot), 20 tons / ha (8 kg/plot), 30 t / ha (12 kg/plot) and the second factor is the guano fertilizer, 100 kg / ha (40 gram/plot), 200 kg / ha (80 gram/plot), 300 kg / ha (120 gram/plot). Parameters measured were plant height, days to flowering, fruit length, fruit diameter, harvesting age, fresh fruit weight and fruit weight per plot. The data obtained were statistically analyzed using analysis of variance followed by Duncan's multiple range test at 5%. The result show that the best dose for enhancing chili growth and production is 20 ton/ha (8 kg/plot) sawdust ash and 300 kg/ha (120 gram/plot) guano fertilizer. The best treatment parameters: flowering age, harvesting age, fruit length, fruit diameter, and fresh fruit weight, fruit weight per plot. Keywords: chili,sawdust ash, guanofertilizer and peatland